“A Made Up Thing” Full of Depth: The Queer Belonging of Robert Duncan and New Narrative - Robin Tremblay-McGaw (Sillages Critiques)
This essay argues that Robert Duncan’s conception of his poet self as “a made up thing and at the same time a depth in which my being is” from The Years as Catches links his poetics to his sexuality and that Duncan, at the center of the San Francisco Bay Area “poetry wars,” becomes a source of grand permission in “queer belonging” for New Narrative writers, specifically Robert Glück and Bruce Boone. New Narrative writers turned from the mainstream’s devastating and violent image of gays and lesbians and the Language writers’ desire to jettison the subject from their own writing to Duncan and Jess [Collins] for the power and pleasures of the made up, fragmented, collaged – a material based relational art, a set of practices, performing queer belonging that looks back in order to move forward, that articulates “the history of our times” and the possibility of a future.